A Chromosome-Scale Genome Assembly of the Okapi (Okapia johnstoni). (5th July 2022) - Winter, Sven; Coimbra, Raphael T F; Helsen, Philippe; Janke, Axel
Abstract: The okapi ( Okapia johnstoni ), or forest giraffe, is the only species in its genus and the only extant sister group of the giraffe within the family Giraffidae. The species is one of the remaining large vertebrates surrounded by mystery because of its elusive behavior as well as the armed conflicts in the region where it occurs, making it difficult to study. Deforestation puts the okapi under constant anthropogenic pressure, and it is currently listed as "Endangered" on the IUCN Red List. Here, we present the first annotated de novo okapi genome assembly based on PacBio continuous long reads, polished with short reads, and anchored into chromosome-scale scaffolds using Hi-C proximity ligation sequencing. The final assembly ( TBG_Okapi_asm_v1 ) has a length of 2.39 Gbp, of which 98% are represented by 28 scaffolds > 3.9 Mbp. The contig N50 of 61 Mbp and scaffold N50 of 102 Mbp, together with a BUSCO score of 94.7%, and 23 412 annotated genes, underline the high quality of the assembly. This chromosome-scale genome assembly is a valuable resource for future conservation of the species and comparative genomic studies among the giraffids and other ruminants.